Structured multidisciplinary discussion of HRCT scans for IPF/UIP diagnosis may result in indefinite outcomes - Pezzuto, Gabriella; Claroni, Giulia; Puxeddu, Ermanno; Fusco, Armando; Cavalli, Francesco; Altobelli, Simone; Portalone, Silvia; Zompatori, Maurizio; Simonetti, Giovanni; Saltini, Cesare; Sergiacomi, Gianluigi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Recent ATS/ERS/JRS/ALAT guidelines for the diagnosis and management of Idiopathic Pulmonary Fibrosis (IPF) have defined key features and specific high-resolution computerized tomography (HRCT) patterns for the diagnosis of UIP. The aim is the sorting of patients with suspected IPF into three subgroups, confident, possible or inconsistent with UIP patterns, after a multidisciplinary discussion (MDD). Specialists in respiratory diseases, radiologists and pathologists should reach IPF diagnosis based on either patients’ clinical, radiological and laboratory data, either submitting patients to surgical biopsy. After ATS/ERS/JRS/ALAT recommendations have been applied, it has been identified a subgroup of patients showing uniform apical-basal distribution of honeycombing and reticular abnormalities that could not be categorized as confident, or possible nor inconsistent with UIP. These patients were subsequently diagnosed with IPF after MDD and lung biopsy. Inclusion of this pattern in the recommendation for IPF diagnosis would be worth considering.